Maqasid al-Shari'a: A tool of mediation in the politics of the Egyptian Supreme Constitutional court - Khalil, Reem Shehab (AUC Knowledge Fountain, 2016)
Maqasid al-Shari’a is a term that is widely used nowadays in the field of Islamic law. However, since the beginning of the 1990s, the Supreme Constitutional Court (SCC) of Egypt, in its interpretation of Article 2 of the Egyptian Constitution, started endorsing the maqasid as a framework through which it conceptualizes the application of Islamic law. Also, with Islamists and religious figures using the maqasid as a framework to use reason and adopt the traditional Islamic jurisprudence to the modern contexts, it is essential to trace how the classical theory of maqasid was developed and what are the constituents of that theory. This paper, accordingly, traces the classical theory of maqasid versus how it has been used since the ‘revival’ of the theory in the late 19th century by Rashid Rida. Accordingly, with such investigation of the roots of the theory and how the classical jurists conceptualized its application, this paper analyzes the SCC’s use of maqasid to demonstrate how the maqasid was a tool used by the court to mediate between different political actors, specifically between the militant Islamists in the 1990s and the secular government.